Pengukuran Mutu Layanan Kesehatan Dasar Gratis Sebagai Perwujudan Hak Sehat Bagi Masyarakat Sukoharjo - Srinugroho, Arif Julianto; Prasetyo, Jarot; Nursito, Sarwono (Kiat Bisnis, 2013)
In order to increasing publicâs welfare, especially in health, Sukoharjo regent made one policy to create primary health service charge of free in community health center to the public without differentiate the socioeconomic status, with 2009 decision Letters of Sukoharjo Regent, No 02. In performing this policy, there is much problem both technical and operational. This research is aimed at investigating external people satisfaction in public health care services, Dinas Kesehatan Kabupaten Sukoharjo, 100 people are chosen as samples with Servqual model.The research illustrates that the Servqual model as a useful managerial tool can be applied in identifying areas to which management resources should be allocated in order to improve and enchance the quality of serviceÂ the Dinas Kesehatan Intitution. The result shows that most servqual model factors: tangibles, reliabilities, assurance, responsiveness, empathies are less satisfied than it should be. Keywords : community health center, servqual, satisfaction